As representações da Revolução e do feminino no cinema cubano : Retrato de Teresa (1979), No hay sábado sin sol (1979), Hasta cierto punto (1983) e Los pájaros tirándole a la escopeta (1984) - Natália Iglésias da Silva Scheid (2019)
This thesis strives to investigate the representations that were created and disseminated by Cuban cinema about Cuban women on the 1970s and 1980s. We seek to understand which was cinema's role on defining and stablishing a new social and political place for the Cuban women. And also how the Revolution itself was represented on these screens. For such, we analyze four Cuban films produced by the ICAIC: Retrato de Teresa (1979), by director Pastor Vega, No hay sábado sin sol (1979), by Manuel Herrera, Hasta cierto punto (1983), by Tomas Gutiérrez Alea and Los pájaros tirándole a la escopeta (1984), by Rolando Díaz.